PERAN JURNALIS SELAMA PANDEMI COVID-19 MELALUI PEMBERITAAN DI KOTA BENGKULU - SAPTA SARI; BAYU RISDIYANTO (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
The role of journalists through reporting in presenting facts and educating the public is part of the social media responsibility. The purpose of writing this article is to see an overview of the role of journalists during the Covid-19 pandemic through the news of the Rakyat Bengkulu Daily Facebook account in Bengkulu City. This role is seen from the point of view of social responsibility theory which focuses on independent media, objective and accurate reporting and elements of education to the community. The results of the study revealed that the role of journalists through reporting on the Rakyat Bengkulu Daily Facebook account during the Covid-19 pandemic was quite good by utilizing independent media so that they could present news that was objective, accurate and contained educational issues so that social media responsibility could be carried out properly.